On the Nature of Particulate Manganese in Simulated Lake Waters - Werner Stumm; R. Giovanoli (CHIMIA)
The oxidation of simulated lake waters incipiently containing 10-5 mol/l Mn2+ leads to the formation of a stable phase: γ-MnOOH. Because γ-MnOOH formed in most natural waters is of colloidal dimensions this phase will not be detected routinely. It is postulated that γ-MnOOH is the final product of an oxidation sequence with Mn3O4 as intermediate.